A Mediterranean-style breakfast increases postprandial serum α-tocopherol levels in lean and obese individuals - García-Rodríguez, S.; Sinausia, L.; Barragán, C.; Montero, E.; Perona, J. S. (Grasas y aceites (Sevilla), 2018)
The aim of this study was to compare the variations in the concentrations of tocopherols and retinol in obese adults in the postprandial state after the intake of a Mediterranean or Western-style breakfast. The study was designed as a randomized, controlled intervention trial in the postprandial state, for which 24 male adults (12 obese and 12 of normalweight) were recruited. After a fat challenge, blood samples were collected at different times postprandially and α-tocopherol, γ-tocopherol and retinol concentrations were determined in serum by HPLC. The Mediterranean-style meal produced a greater increase in serum α-tocopherol levels in both obese and normal-weight subjects, compared to the Western-style meal, indicating that the composition of the food affects the concentration of tocopherols in the postprandial state. However, the serum concentrations of γ-tocopherol and retinol remained unmodified. In conclusion, the presence of α-tocopherol in the meal could contribute to the protection of the Mediterranean-style meal against atherosclerosis in the postprandial state.